Token Non-Fungible (NFT) sebagai Instrumen Investasi Seni Berbasis Blockchain - Donny Trihanondo; Soni Sadono (Ideas Publishing, 2023)
Recently, conventional art assets and those in the form of NFTs have experienced significant price increases. The purpose of this research is to raise the NFT phenomenon in art activities in Indonesia. Researchers used qualitative methods with an emphasis on observation and literature studies to obtain data. The research results show that the NFT market has the potential to be a place of various scams. Then, as NFT creators, artists are only given tantalizing images, especially those related to the metaverse. Meanwhile, NFT in the near future cannot replace conventional works of art. In conclusion, NFT is beneficial for artists, but the challenge is that metaverse developers must provide a creative medium that is safer from fraudulent acts.